Mapping Emotional Intelligence Research in Islamic Education: A Bibliometric Study on the Integration of Emotional Intelligence - Septariani, Sella Fadia; Bary, Akmal (Universitas Muhammadiyah Yogyakarta, 2026)
This study develops a conceptual framework and thematic outline of Emotional Intelligence (EI) research in Islamic education using a bibliometric approach. Data were collected from Google Scholar through Publish or Perish (PoP) using the keywords “emotional intelligence” and “Islamic education” in titles, abstracts, and author keywords. The initial search identified 200 publications from 2010 to 2025. After screening for relevance, duplication, and metadata completeness, 150 publications were selected for analysis. Using VOSviewer, bibliometric techniques were applied to examine publishing trends, citation patterns, co-authorship networks, co-citation relationships, and keyword co-occurrence. The findings reveal a sustained global increase in scholarly interest in applying emotional intelligence within Islamic education. Emotional intelligence emerges as the central construct, closely linked to spiritual intelligence, multiple intelligences, and Islamic educational psychology. Visualization mapping indicates a shift from predominantly theoretical discourse toward more comprehensive and practice-oriented research, including instructional strategies, curriculum development, and institutional roles. The study highlights the originality of identifying a neglected triadic relationship among emotional intelligence, spiritual intelligence, and learning motivation. Although conceptually connected, empirical investigations of their combined influence remain limited. This research maps the scholarly landscape, identifies underexplored areas, and provides direction for future empirical studies integrating emotional and spiritual dimensions to enhance motivation, moral reasoning, and holistic student development in Islamic education.